Digitalization of The Transaction Management and Financial Reporting System at D'jakarta Barbershop - Nabillah Indah Tsuraya; Zahra Khanza Aurilia; Fajar Ilhami Indo Syaputra; Aji Setiawan; Herianto (Fakultas Teknik Universitas Darma Persada, 2026)
Barbershop D'Jakarta is a hair care business that requires integrated transaction and financial management to ensure efficient business operations. This study aims to design and develop a web-based financial and operational management information system using the Laravel 11 framework with a MySQL database. The system was developed using the Waterfall method and is divided into two user roles: Owner and Admin. Key features include a home screen (START), authentication, an adaptive dashboard, account and employee management, products/services, customers, two-step transactions with JPEG payment proof upload, expenses, monthly targets, statistics along with employee rankings, and automatically numbered PDF financial reports. The interface is built with custom, responsive CSS and supports both light and dark modes. Black-box testing results show that all features function as required with a 100% success rate. This system has proven to replace manual record-keeping, improve data accuracy, and make it easier for owners to monitor business performance in real time.